Guide :

# I have a regression formula of y=4.955*x+(286.516). I am told to find the answer when x =15

X and Y Coordinates to get  the regression formula y=4.955*x+(286.516) are (0,280), (2,300), (5,317), (6, 319), (7,324), (8,322), (9,328), (10,335).  We are asked to find y when x =15.

## Research, Knowledge and Information :

### Using Excel statistical functions for trend analysis ...

... row of the answer array in reverse order. Y = 18.84 ... Excel statistical functions for trend ... I am trying to make a formula to know y when I ...

### Probability and Statistics for Engineers and Scientist part 2 ...

... Ryan Copeland, Name: Probability and Statistics for Engineers ... regression? Justify your answer ... x a m p l e 12.15 we m a y wish to ...

### (MULTIPLE REGRESSION(FULL MODEL) Model Summaryb Change ...

... (FULL MODEL) Model Summaryb Change Statistics Model 1 R R Square .822a ... 980 6147300089201.100 .000c 725 Regression 286.659 2843121218 ... 15 4 2.9 4 2.9 17.7 ...

### More Complex Regression Models - Springer

More Complex Regression Models. ... See 15 U.S.C. §78u-4(e) ... The role of OLS regression in this context is solely to produce an adjustment formula to define the ...

### User Manual for Laz Stats | Regression Analysis - Scribd

User Manual for Laz Stats ... Fig. 4.14 Polynomial Regression Smoothing Form 113 Fig. 4.15 Plot of Polynomial Smoothed ... We can expand the above formula as Y = (X 1

### 11 (number) - Wikipedia

Example 2: 481 x 11 becomes 4 (4+8) (8+1) 1 or 4 (10+2) 9 1 or (4+1) 2 9 1 ... 15: 11 ÷ x: 11: 5.5: 3. 6: 2.75: 2.2: 1.8 3: 1. 571428: 1.375: 1 ... ("I told you ...

### WWWFinance - Optimal Portfolio Control: Campbell R. Harvey

Note in terms of our formula for Taylor series: x=W ... 1.296 1.286 1963 8.380 2.735 ... 12.437 4.955 21 ...

The following sample observations were randomly selected X: 5 3 6 3 4 4 6 8 Y: 13 15 ... If I have a formula ... Hi I am performing a regression analysis with 3 x ...

## Suggested Questions And Answer :

### I have a regression formula of y=4.955*x+(286.516). I am told to find the answer when x =15

Thats formula for strate line y=4.955x +286.516 EVALUATE at x=15... 4.955*15+286.516...4.955*15=74.325 =360.841

### the perimeter of a rectangle is 66cm and it's width is half its length. what are the length and width of the rectangle

First let's state the formula for perimeter of a rectangle: Perimeter = 2(length) + 2(width) OK, for this rectangle let's set the length equal to x length = x Now we are told that the width is one half it length.  So if the length is x then width = 1/2*(x) or x/2 OK, the problem also tells us that the perimeter is 66 cm Now we have everything we need to use the perimeter formula and solve for x Perimeter = 2(length) + 2(width) 66 = 2(x) + 2(x/2) 66 = 2x + x 66 = 3x 22 = x Answer: the length is 22 cm Now use this value for length to find the width width = x/2 width = 22/2 width = 11 Answer: the width is 11 cm  Check both answers by using the perimeter formula. Perimeter = 2(length)+2(width)  66 = 2(22) + 2(11) 66 = 44 + 22 66 = 66

### help me to solve this problem.

Given that y varies jointly with x and with the square root of z, and that y=2 when x=1/8 and z=1/4 , so find i. a formula giving y in terms of x and z, and ii. the value of y when x=3/8 and z=1/9.   When we are told the y varies jointly with two things then that means y is proportional to the product of these two things, i.e. y is some constant times that product. So, y = k*x*sqrt(z), or y = k.x.sqrt(z) Initial conditions i.e. y=2 when x=1/8 and z = 1/4, so 2 = k.(1/8).sqrt(1/4) 2 = k.(1/8).(1/2) = k.(1/16) Therefore, k = 2*16 = 32 Then y = 32.x.sqrt(z) The value of y when x=3/8 and z=1/9. We have y = 32.x.sqrt(z). Substituting for x = 3/8 and z = 1/9, y = 32.(3/8).sqrt(1/9) y = 32.(3/8).(1/3) y = 32.(1/8) Answer: y = 4

### How do I find the answer to (10/11)² - 1/11 • 1 1/12 ? No matter how I work it I'm told my answer is wrong.

How do I find the answer to (10/11)² - 1/11 • 1 1/12= ? No matter how I work it I'm told my answer is wrong. Note: 99 119/132 isn't the answer. I got that by (10/11)² = 100/121, 1/11 • 1 1/12= 13/132, so 100/121 - 13/132 = 99 119/132 Please note that your last computation, 100/121 - 13/132 = 99 119/132 is where you went wrong. You final result, 99 119/132, you would get from, 100 - 13/132 = 99 119/132. It looks as though you simply forgot to divide by 121! The answer is: 100/121 - 13/132 = (100*132 – 13*121) / (121 * 132) 100/121 - 13/132 = (13200 – 1573) / (15,972) 100/121 - 13/132 = (11,627) / (15,972) = 1057/1452  (take out a factor of 11, top and bottom) Answer: 1057/1452

### What are the three formulas for calculating any percentage question on a calculator?

For converting a fraction into a percentage multiply by 100. Example: 1/4 multiplied by 100 is 25 percent. For converting a percentage into a fraction, divide by 100. Example: 75% is 75/100=3/4. Formula 1. For answering the question: What number is p% of n? Call the number y, then y=np/100. Example: what number is 2% of 450? y=450*2/100=9. Formula 2. For answering the question: y is what percent of n? Call the percentage p. y=np/100, so p=100y/n. Example: 15 is what percent of 250? p=100*15/250=6%. Formula 3. For answering the question: y is p% of what number? Call the number n=100y/p. Example: 16 is 12.5% of what number? n=100*16/12.5=128. Note that there's really only one formula, which converts a percentage into a fraction. It's just a matter of taking the two known quantities and rearranging the formula to find the missing unknown.

### How to find the nth formula of a sequence with numbers 0,1,3,6,10

The formula for the nth term is n(n+1)/2, where n=0, 1, 2, etc. To derive this formula for the sum of the natural numbers up to n, we use the fact that the average of the first and last numbers (0 and n), the average of the second and penultimate numbers (1 and n-1), etc. is constant, and we have n+1 of these, hence the formula.

### how do i find the solution set of 2(5x+20)=2(6x+12)?

Given 2(5x+20)=2(6x+12) 10x+40=12x+24 10x-12x=24-40 -2x=-16 x=8 Algebra Word Problems

### Help me understand this qiestion

It seems we're trying to calculate the linear regression equation y=mx+b. The given summations enable us to calculate what we need to find m and b. And we're given that the dataset has 8 pairs of (X,Y) elements. We use this number to find mean values. ∑X/8 = Xm the mean or average of the X's. ∑Y/8 = Ym the mean of the Y's. ∑X^2/8 = Xms the mean of the squares of X. ∑XY/8 = XYm the mean of the products of X and Y. m=(XmYm-XYm)/((Xm)^2-Xms). Xm=680/8=85; Ym=2575/8=321.875; XYm=241400/8=30175; Xms=62600/8=7825. So m=(85*321.875-30175)/(7225-7825)=4.693 approx. b=Ym-mXm=321.875-4.693*85=-77.03; y=4.693x-77.03 is the linear regression equation, in which y is the cost and x is the power. We can write this Cost=4.693*Power-77.03 so that it's clear what the variables are. From this it seems the first answer in the list of possible answers is the right one: Cost=-77.005+4.693(Power).  (The small discrepancy in the constant is due to rounding. A more accurate estimate of m is 4.6927. This value gives b=-77.0045.)

### if a shape has 88 area , 52 perimeter what is the length and breadth?

????????? bredth ?????????? perhaps yu meeeeeeen wide ???????yu hav a shape ?????????? yer spozed tuno its a rektangel formula for area & rim length depend on wot shape it is 1 formula for serkel, diff formula for square, dif formula for polygons

### 2x^2 + 32x + 119 = 0 write your answer in surd form

To find roots of a quadratic equation, first try if it could be simply factorized into (x-a) (x-b), so the roots will be x = a or x = b. If it's not easily factorized that way, then, use this quadratic formula: x = [-b + √(b² - 4ac)] / 2a and x = [-b - √(b² - 4ac)] / 2a Now, to use the quadratic formula above, the format of quadratic equation must be in the form of ax²+bx+c = 0 If the quadratic equation is 2x²+32x+119=0, then: a = 2 b = 32 c = 119 Put a, b, and c values to the formula x = [-b + √(b² - 4ac)] / 2a x = [-32 + √(32² - 4*2*119)] / (2*2) x = [-32 + √(1024 - 952)] / 4 x = (-32 + √72) / 4 --->simplify √72, remember that 72 is 36*2 x = [-32 + √(36*2) ]/ 4 ----> remember that √(a*b) = √a*√b x = [-32 + (√36*√2)] / 4 --->√36 = 6 x = [-32 + (6*√2)] / 4 x = (-32 + 6√2) / 4 x = -32/4 + (6/4)(√2) x = -8 + 1.5(√2) From other quadratic formula, x = [-b - √(b² - 4ac)] / 2a we will have: x = -8 - 1.5(√2) If x = p+q(√2), hence: p = -8 q = 1.5 or q = -1.5